Development and Validation of a Morbidity and Mortality Prediction Score for Proximal Femur Fracture Patients with Comorbidities - Yash Ratanpal; Ravindra B. Gunaki (Journal of Neonatal Surgery, 2024)
Proximal femur fractures in elderly patients are associated with high morbidity and mortality, primarily due to the presence of multiple comorbidities and adverse lifestyle factors. This study aimed to develop and validate a comorbidity index to assess the risk of postoperative complications and mortality in elderly patients undergoing surgery for proximal femur fractures. A mixed-methods approach was used, combining both prospective and retrospective data from 100 patients, each followed at various intervals post-surgery (immediate, 3 months, 6 months, and 1 year). The comorbidity index included key predictors such as age, pre-fracture mobility, anemia, diabetes mellitus, hypertension, ischemic heart disease, renal disease, dementia, alcohol dependence, and tobacco use. Statistical analysis revealed that higher comorbidity scores were significantly correlated with increased mortality and complications, with dementia, ischemic heart disease, and renal disease showing the strongest associations. Kaplan-Meier survival analysis confirmed that patients with comorbidity scores above 10 had markedly lower survival rates over one year. The comorbidity index proves to be a valuable tool for preoperative risk stratification, enabling tailored, multidisciplinary care that can improve postoperative outcomes for high-risk patients. Future research should focus on further validating this index and investigating targeted interventions for patients with elevated comorbidity burdens.